2019
DOI: 10.1029/2019gb006276
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Respiration Pulses in Intermittent Rivers and Ephemeral Streams

Abstract: Intermittent rivers and ephemeral streams (IRES) may represent over half the global stream network, but their contribution to respiration and carbon dioxide (CO2) emissions is largely undetermined. In particular, little is known about the variability and drivers of respiration in IRES sediments upon rewetting, which could result in large pulses of CO2. We present a global study examining sediments from 200 dry IRES reaches spanning multiple biomes. Results from standardized assays show that mean respiration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 45 publications
2
35
0
1
Order By: Relevance
“…These could be, for instance, organic matter quality/lability, the presence of terrestrial vegetation (primary production), CO 2 inputs via groundwater discharge, composition of the microbial community, or carbonate formation, which previous studies have identified as being potentially important 16,17 . Finally, antecedent conditions such as the time since desiccation or the past input of organic matter into the system may also influence CO 2 emissions 37,38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These could be, for instance, organic matter quality/lability, the presence of terrestrial vegetation (primary production), CO 2 inputs via groundwater discharge, composition of the microbial community, or carbonate formation, which previous studies have identified as being potentially important 16,17 . Finally, antecedent conditions such as the time since desiccation or the past input of organic matter into the system may also influence CO 2 emissions 37,38 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, rewetting events are short periods of high biogeochemical activity that may contribute significantly to CO 2 fluxes 42 and are not purposely included in our estimates. Rapid pulses of CO 2 production following rewetting have been observed in a variety of soil ecosystems 42,43 as well as in dry river beds 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, dos trabajos recientes en arroyos temporarios, realizados en 29 países entre los cuales se incluyeron arroyos temporarios de la cuenca del Challhuaco, demostraron que en el momento en que estos arroyos vuelven a tener agua se liberan grandes cantidades de CO 2 tanto por descomposición de la hojarasca acumulada en el lecho seco (Datry et al 2018) como desde los sedimentos (Von Schiller et al 2019). En particular, se halló que los sedimentos con mayor cantidad de materia orgánica, con menores valores de C:N y mayor cobertura ribereña, en cuencas naturales y más húmedas, como las andino-patagónicas, eran las que liberaban mayores cantidades de CO 2 a la atmósfera.…”
Section: Cambio Climáticounclassified
“…During flow cessation and dry period, IRES accumulate a diversity of substrates, especially of terrestrial plant litter, biofilms, animal carcases, and sediments, considered as biogeochemical reactors or hot spot areas. These substrates generate high O 2 consumption and CO 2 release rates, with a notable impact on the global CO 2 flux through atmospheric emissions [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%